2023
DOI: 10.1007/s13555-023-00940-0
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Concurrent Psoriasis and Hidradenitis Suppurativa Successfully Treated with Tildrakizumab

Abstract: Introduction Plaque psoriasis and hidradenitis suppurativa are chronic inflammatory skin conditions with common pathogenetic pathways. Methods We report the case of a 38-year-old man with 15-year history of psoriasis and hidradenitis suppurativa successfully treated with tildrakizumab for both conditions. After treatment failure to adalimumab, secukinumab, and guselkumab, tildrakizumab therapy was initiated and resulted in complete remission of psoriasis and the achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The results were confirmed at week 52, and the authors reported no side effects. 22 The other case described in the literature concerns a case of a 50-year-old patient affected by PASH syndrome who had had a significant worsening of HS; 23 the patient had practiced in the past with only limited benefit unspecified antibiotic therapy and adalimumab (interrupted for ineffectiveness); therefore, the authors report having started treatment with tildrakizumab. At baseline, the patient had an abscess and nodule count of 45, DLQI score of 26, and visual analog scale (VAS) pain score of 10 was reported.…”
Section: Resultsmentioning
confidence: 99%
“…The results were confirmed at week 52, and the authors reported no side effects. 22 The other case described in the literature concerns a case of a 50-year-old patient affected by PASH syndrome who had had a significant worsening of HS; 23 the patient had practiced in the past with only limited benefit unspecified antibiotic therapy and adalimumab (interrupted for ineffectiveness); therefore, the authors report having started treatment with tildrakizumab. At baseline, the patient had an abscess and nodule count of 45, DLQI score of 26, and visual analog scale (VAS) pain score of 10 was reported.…”
Section: Resultsmentioning
confidence: 99%